2006
DOI: 10.1103/physrevb.74.165112
|View full text |Cite
|
Sign up to set email alerts
|

Nature of the two quantum critical points inCe(Ru1xRhx)2et al.

Abstract: The magnetic phase diagram of Ce͑Ru 1−x Rh x ͒ 2 Si 2 contains a spin-density-wave ͑SDW͒ magnetic ordering temperature approaching T = 0 at both x Ϸ 0.03 and 0.35-0.4 ͑i.e., a dome-shaped phase boundary͒ and long range, local moment antiferromagnetism, T N = 36 K, in pure CeRh 2 Si 2 suppressed with Ru doping to T =0 at x Ϸ 0.6-0.65. This latter possible second quantum critical point ͑QCP͒, and the possible interplay between the fluctuations caused at each of the two QCP's, are investigated here using specific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…We therefore investigated the alloys, CeRu 2-x Rh x Si 2 , crystallizing in ThCr 2 Si 2 -type tetragonal structure. The compound, CeRu 2 Si 2 , is a well-known non-magnetic Kondo lattice far away from QCP [9,10], while x =1.2 alloy is at QCP [11]. Earlier [6], on the basis of initial magnetization studies, we reported that, CeRu 2 Si 2 undergoes some kind of magnetic ordering in the fine particles of this compound.…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…We therefore investigated the alloys, CeRu 2-x Rh x Si 2 , crystallizing in ThCr 2 Si 2 -type tetragonal structure. The compound, CeRu 2 Si 2 , is a well-known non-magnetic Kondo lattice far away from QCP [9,10], while x =1.2 alloy is at QCP [11]. Earlier [6], on the basis of initial magnetization studies, we reported that, CeRu 2 Si 2 undergoes some kind of magnetic ordering in the fine particles of this compound.…”
Section: Introductionmentioning
confidence: 84%
“…It is now established [11] in the literature that a partial replacement of Ru by Rh drives Ce towards magnetic ordering in the bulk form, with x = 1.2 alloy lying at the quantum critical point, exhibiting non-Fermi liquid behavior (NFL) in its properties (for example, logarithmic divergence of C/T at low temperatures). In view of the observation of magnetic ordering in the nanoform of CeRu 2 Si 2 , it is important to see whether the same is observed at the QCP.…”
Section: Ceru 08 Rh 12 Simentioning
confidence: 99%